Influence of wood grain variations on some physical and mechanical properties of laminated veneer lumber - Elif Duran; Vedat Çavuş (Turkish Journal of Forestry)
Laminated veneer lumber is a composite of layers of wood veneers and glues. Laminated veneer lumber, which is a building material, is formed by gluing the veneers obtained by peeling method by aligning them parallel to each other in the fiber direction. In this study, some physical and mechanical properties of laminated veneer lumber produced with Eastern Beech (Fagus orientalis L.) and the fiber orientation was changed at different angles in certain layers were investigated. Polyurethane glue was preferred in this study. For the experiments, 1 control group and 2 experimental groups were prepared. The laminated veneer lumber was produced in 11 layers. In the manufacturing of the test specimens, the fiber orientation of the laminated veneer lumber was produced as Control, 0°90°0° and 0°90°45°0° to coincide with the tensile direction opposite to the compression direction. The specimens were tested for physical properties such as air and oven dry density, water absorption and thickness swelling, and mechanical properties such as flexural strength, flexural modulus of elasticity, dynamic flexural strength, Janka hardness, screw holding capacity and tensile shear strength. It was found that fiber orientation causes a decrease in the physical and mechanical properties of laminated veneer lumber. It was determined that for the control, 0°90°0° and 0°90°45°0° test specimen groups; 3.8%, 32.4%, 15.42%, 26.08%, 9.67% and 9.31% decrease occurred in bending resistance values, modulus of elasticity in bending values, dynamic bending resistance values, respectively. For the control, 0°90°0° and 0°90°45°0° test specimen groups; 2.48%, 14.44%, 40%, 31.52%, 4.21%, 28.13%, 4.21% and 28.13% decrease in static hardness values, tensile-shear resistance, and screw holding capacity, respectively.